George W. Hess, Revised Ordinances of the City of Evanston: Also Special Laws and Ordinances of General Interest 137 (1893) - (:unkn) unknown (My University, 1893)
§§ 537-538: Licenses may be granted by the mayor at the mayor's discretion. Licenses are also revoked at the mayor's discretion. Applications shall be submitted to the city clerk with a payment of two dollars.
Keywords: REGISTRATION